2016
DOI: 10.4103/2229-5151.177359
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and outcome of traumatic brain injury in children <15 years: A tertiary level experience in India

Abstract: Background:Though, traumatic brain injury (TBI) has been documented as the single most common cause of morbidity and mortality in infancy and childhood, the exact incidence is unavailable in India. Moreover, modes of injury, mechanisms of damage, and management differ significantly from that of an adult.Aims and Objectives:To analyze the epidemiological factors, the spectrum of TBI, modes of injury, types of injury, and the outcome in the children <15 years with TBI.Materials and Methods:This is a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 19 publications
(30 reference statements)
13
18
0
Order By: Relevance
“…Head CT scan was ordered in 70.7% of study subjects and showed various types of skull bone fractures, brain contusion, intracranial bleeding, and diffuse axonal injury. ese findings are in agreement with studies done in India, Tunisia, and Nigeria, and head CTscan requests conform to the recommended neurosurgical practice [22,25,30,37,39].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Head CT scan was ordered in 70.7% of study subjects and showed various types of skull bone fractures, brain contusion, intracranial bleeding, and diffuse axonal injury. ese findings are in agreement with studies done in India, Tunisia, and Nigeria, and head CTscan requests conform to the recommended neurosurgical practice [22,25,30,37,39].…”
Section: Discussionsupporting
confidence: 91%
“…Concerning mechanisms of injury, unintentional pedestrian RTA and falls were the most common causes followed by intentional fights/violence injuries. is is in line with most of the studies done in developing countries [2,8,18,22,30,34,[37][38][39].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…5,6 There are many studies on trauma in children; they mainly represent the scenario in developed countries. There is a paucity of studies from developing countries like India.…”
Section: Discussionmentioning
confidence: 99%